(untitled) (Academic Journal of Internal Affairs, 2023)
Aim: One of the defining features of modern society is the legitimate fear of the impacts of environmental damage. The consumerism and the resulting overproduction are the root causes of environmental challenges that threaten our very existence. This study aims to investigate the role of criminal law in environmental protection. Methodology: Empirical analyses were conducted on the contents of finalized criminal cases in Borsod-Abaúj-Zemplén county and Csongrád-Csanád county from the years 2009 to 2018. Findings: The findings reveal that the primary role of environmental criminal law is to safeguard regulations related to environmental use. Analysis of Hungarian criminal cases involving environmental harm and damage to nature show that the majority of cases were not related to production or manufacturing practices. Value: This study presents a theoretical model that categorizes actions causing environmental harm into four groups, irrespective of their legality. Drawing on empirical evidence from criminal and administrative procedures, the study suggests potential directions for future regulatory actions.